Retrofitting of an existing RC structure using EC8 - Part 3 - Chrysostomou, Christis; Kyriakides, Nicholas; Pittas, Michael (My University, 2010)
A building that was designed, detailed and constructed in 1960 in Cyprus for gravity loads only was selected as a case-study for a pilot application of Eurocode 8 part 3. The information collected, the assessment and the retrofit of the structure are described here. It can be concluded that: 1) EC8 part 3 is a workable code that can guide the engineer through the assessment and retrofit process, 2) the knowledge level factor does not affect the capacities of ductile elements but it changes significantly those of brittle elements; for this building it may not be cost-effective to try to move from knowledge level 2 to knowledge level 3, 3) The nonlinear static method, provided it can be applied, gives a quantitative insight in the assessment and retrofit process, 4) A dedicated software is required for the application of the code, due to the considerable amount of calculations needed in determining the deformations of all the members and comparing them to the deformation capacities and 5) this code can be used for the assessment of individual buildings but it would be very costly to use it for the screening of a large number of buildings.
Keywords: EC8 part 3; Seismic performance assessment; Seismic retrofitting